EFFORTS TO INCREASE NUTRITION FOR FAMILY OF TOGETHER WITH THE UTILIZATION OF YARD LAND IN TANJUNG HARAPAN VILLAGE - Bardiati ulfah (Borneo Community Development, 2022)
Balanced nutrition is defined as a daily diet that contains substances in the types and amounts that are in accordance with the body's needs. Most families of toddlers still have limited knowledge about the importance of the nutritional value consumed, especially vegetables and fruit, the important mindset is that side dishes and rice are sufficient to meet family nutrition, which is one reason not to consume vegetables and fruit. Other inhibiting factors for fulfilling nutrition, namely family income, people's purchasing power to meet their daily needs, it is not easy to find it difficult to get vegetables and fruit because of the remote location and swamp land for vegetable cultivation in the Tanjung Harapan village area, causing some under-nourished toddlers and families of toddlers sick often